Potential of Bioactive Protein and Protein Hydrolysate from Apis mellifera Larvae as Cosmeceutical Active Ingredients for Anti-Skin Aging - Paphawarin Thuraphan; Suphawan Suang; Anurak Bunrod; Watchara Kanjanakawinkul; Wantida Chaiyana (MDPI AG, 2024)
This study aimed to extract bioactive proteins and protein hydrolysates from Apis mellifera larvae and assess their potential application in cosmetics as well as their irritation properties. The larvae were defatted and extracted using various mediums, including DI water, along with 0.5 M aqueous solutions of sodium hydroxide, ascorbic acid, citric acid, and hydrochloric acid. Subsequently, the crude proteins were hydrolyzed using the Alcalase® enzyme. All extracts underwent testing for antioxidant activities via the 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) and Griess assays. Anti-aging properties were evaluated in terms of anti-collagenase and anti-hyaluronidase effects. Irritation potential was assessed using the hen's egg chorioallantoic membrane (HET-CAM) test. The results revealed that the sodium hydroxide extraction showed promising outcomes in terms of yield, protein content, and effectiveness in inhibiting hyaluronidase, with the highest inhibition at 78.1 ± 1.5%, comparable to that of oleanolic acid. Conversely, crude protein extracted with ascorbic acid and its hydrolysate showed notable antioxidant and collagenase-inhibitory activities. Remarkably, their anti-collagenase effects were comparable to those of ascorbic acid and lysine. Additionally, it demonstrated safety upon testing with the CAM. In conclusion, the findings provided valuable insights into the utilization of A. mellifera larval proteins as active ingredients with a wide range of cosmeceutical applications, particularly due to their antioxidant, anti-aging, and low irritation properties, which hold significant promise for anti-skin wrinkles.